Stress resistance associated with multi-host transmission and enhanced biofilm formation at 42 °C among hyper-aerotolerant generalist Campylobacter jejuni. (May 2021) - Mouftah, Shaimaa F.; Cobo-Díaz, José F.; Álvarez-Ordóñez, Avelino; Mousa, Ahmed; Calland, Jessica K.; Pascoe, Ben; Sheppard, Samuel K.; Elhadidy, Mohamed
Abstract: One of the emerging conundrums of Campylobacter food-borne illness is the bacterial ability to survive stressful environmental conditions. We evaluated the heterogeneity among 90 C. jejuni and 21 C. coli isolates from different sources in Egypt with respect to biofilm formation capabilities (under microaerobic and aerobic atmosphere) and resistance to a range of stressors encountered along the food chain (aerobic stress, refrigeration, freeze-thaw, heat, peracetic acid, and osmotic stress). High prevalence (63%) of hyper-aerotolerant (HAT) isolates was observed, exhibiting also a significantly high tolerance to heat, osmotic stress, refrigeration, and freeze-thaw stress, coupled with high biofilm formation ability which was clearly enhanced under aerobic conditions, suggesting a potential link between stress adaptation and biofilm formation . Most HAT multi-stress resistant and strong biofilm producing C. jejuni isolates belonged to host generalist clonal complexes (ST-21, ST-45, ST-48 and ST-206). These findings highlight the potential role of oxidative stress response systems in providing cross-protection (resistance to other multiple stress conditions) and enhancing biofilm formation in Campylobacter and suggest that selective pressures encountered in hostile environments have shaped the epidemiology of C. jejuni in Egypt by selecting the transmission of highly adapted isolates, thus promoting the colonization of multiple host species by important disease-causing lineages. Highlights: Oxidative stress defense responses in Campylobacter are associated with enhanced biofilm formation capabilities. Host generalist lineages are better equipped to withstand hostile environmental conditions favoring zoonotic transmission. Multi-stress adapted Campylobacter isolates challenges efforts made to eliminate this foodborne pathogen from the food chain.